METHODS OF USING EFFECTIVE APPROACHES IN TEACHING WRITING IN NON-PHILOLOGICAL HIGHER EDUCATIONAL INSTITUTIONS (IN THE EXAMPLE OF ENGLISH) (Analysis of International Sciences, 2024)
This article explores effective approaches for teaching writing in non-philological higher educational institutions, with a focus on the English language. The aim is to provide educators with practical strategies and considerations that can enhance the writing instruction process. Drawing upon best practices and research in the field, the article presents a range of methods, including writing workshops, authentic audience engagement, reflective writing practices, multimodal approaches, individualized instruction, and cultural and linguistic considerations. It also highlights the importance of authentic assessment, writing across the curriculum, revision and iterative writing, cultural and global perspectives, and ongoing professional development for educators. By implementing these approaches, educators can create a dynamic and student-centered writing curriculum that fosters skills development, critical thinking, and effective communication in English.